Inclusive educational environment in Zaporizhzhia region: results of pilot project implementation - Штефан, А. К. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
Social work in inclusive education is to create conditions for the educational process in which a child with a disability can acquire basic knowledge, skills, social interaction and feedback skills, receive psychological, socio-educational and, if necessary, legal support to meeting their needs. The role of the social worker in the school is leading and undisputed. But modernity requires constant improvement of skills and advanced training. The purpose of the social worker at school is to create a special environment among children. The feedback of a social worker is to overcome fears and prejudices, promote friendships, mutual respect and understanding among students, and improve the cognitive, motor, speech, social, and emotional development of children. The most pressing issue of today’s education system is inclusive education for children with disabilities in a single educational space. Each country has its own experience of special education for children and has gone through a different path from integration to inclusion. Today, in modern Ukraine, the education system is being transformed, the model of inclusive education is gaining wide significance and a new pattern of its development. Attempts to form an inclusive education system have not yet yielded significant results, which is manifested in the constant division of children into «normal majority» and «backward minority». In Ukraine, children with disabilities have long been isolated from their peers. Boarding schools or individual learning provide knowledge, but take away the opportunity to communicate, hinder the socialization of such pupils. This article provides a brief analysis of the pilot project, in accordance with the order of the Ministry of Education and Science dated 15.07.2016 № 836 «On conducting a scientific and pedagogical experiment «Development of an inclusive environment in the Zaporozhye region». Building an effective system of inclusive education in Ukraine is possible on the basis of the interaction of various factors, first of all, strengthening the financing of education, improving its regulatory support, improving the methodological and staffing of inclusive education. The results of the work can be used in further research on this problem.